Ethical values and auditors fraud tendency perception: Testing of gone theory - Fakhroni, Zaki; Setiawan, Faisha Salmaa (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to empirically examine the fraud tendency in external auditors’ perception influenced by components of the gone: greed (G), opportunity (O), need (N), and exposure (E). Furthermore, ethical values (EV) are placed as a moderating variable for this relationship. This is a quantitative study by conducting a survey of 345 external auditors around Indonesia using the snowball method with the Slovin formula. The hypotheses in this study were analyzed using multiple linear regression tests with the SPSS Statistics 29 program. The findings of this study indicate that the four components of gone theory are fully proven as triggers of fraud in the perception of external auditors. Other findings also provide evidence that EV moderates the relationship between all variables, except for greed. This study contributes to the understanding of fraud tendencies among external auditors, moderating role of ethical values, and suggests practical responses to audit profession’s fraud triggers.